PSYCHO-SUFISTIC THERAPY OF UNDERGROUND SUFISM MOVEMENT:A HEALING METHOD AGAINST PUNK COMMUNITY IN JAKARTA - Muaz, Abdul; Ahmad, Adang Darmawan (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2019)
This study imvestigates the psycho-Sufistic therapy applied by the